Livestock Breeders’ Conflicts in the Steppe Rangelands of Naâma Region (Western Algeria) - Toufik, Youcefi Ahmed; Abderrazak, Marouf (Indonesian Journal of Agricultural Research, 2024)
Sheep farming represents a very important activity in the Algerian steppe, unfortunately it is in a critical situation following climate changes, decreases in rangelands and the rise in the prices of livestock feed, this has created conflicting situations between breeders. The competition for access to steppe spaces and the use of natural resources are at the origin of several conflicts between the actors of the steppe. In this article, we tried to present in a brief way the nature and rate of existing conflicts between pastoralists, and compliance with current legislation which aims to protect the plant cover and soil. The approach taken to carry out this analysis is based on a field survey whose target population is the holders of the herd. The sample size exceeds 364 surveyed spread across the 12 municipalities in our study area. Our work shows that one-fifth of respondents suffer from conflectual situations, either against a legal person or natural persons, while four-fifths endure no strife. In addition, the comparison between two periods (2010 - 2014 and 2015 “ 2019) shows that the average number of established and trained offence report by forest administration concerning “illicit grazing” had doubled. The solution consists in cleaning up the steppe against illegal monopolies, accompanied by awareness-raising activities for a better awareness of residents to change their bad behavior. Finally, the competent authorities are required to find alternatives to enable farmers to carry out their activities properly.